Key aspects of numerical analysis of gas hydrate reservoir performance: Alaska North Slope Prudhoe Bay Unit “L-Pad” hydrate accumulation - Ajayi, Taiwo; Anderson, Brian J.; Seol, Yongkoo; Boswell, Ray; Myshakin, Evgeniy M. (Journal of natural gas science and engineering, 2018)
In previous work, we reported the development of the 3D geostatistical hydrate reservoir model of "L-Pad" (Myshakin et al., 2016). In this paper, gas production sensitivity on key reservoir parameters are studied. Hydraulic communication with an aquifer and optimal depressurization strategies are subjects of investigation. Uncertainty in initial in situ permeability within 0.1–10 mD range leads to 2.0 × 108–3.5 × 108 ST m3 of gas produced over 10 years. Accounting for reservoir quality and irreducible water saturation leads to noticeable change in productivity. Sequential depressurization of hydrate-bearing units was found to be more attractive versus simultaneous depressurization. •Reservoir production is evaluated against uncertainty in key model parameters.•Effect of hydraulic communication with an aquifer is estimated.•Depressurization strategies for a double-unit hydrate reservoir are explored.